Drug treatment strategies for paget's disease: relieving pain and preventing progression. (13th April 2023) - Merlotti, Daniela; Rendina, Domenico; Cavati, Guido; Abate, Veronica; Falchetti, Alberto; Mingiano, Christian; Nuti, Ranuccio; Gennari, Luigi
ABSTRACT: Introduction: Paget's disease of bone (PDB) is a focal bone disorder caused by a marked dysregulation of osteoblasts and osteoclasts in basic multicellular units, leading to abnormal and disorganized deposition of collagen fibers (the so-called 'woven bone'). Therefore, pagetic bones are increased in size, and at increased risk for bone pain, deformities, fractures, osteoarthritis, and, more rarely, neoplastic degeneration. Areas covered: In this review, we revise the available information concerning the pharmacological treatment of PDB. Expert opinion: PDB progresses slowly within the affected skeletal sites and, if untreated, often leads to bone overgrowth, with bone pain, deformity, and a likely increased risk of complications. Thus, the primary goal of treatment is the restoration of a normal bone turnover, in order to relieve bone pain or other symptoms and possibly prevent the complications. PDB long remained a poorly treatable disorder until the discovery of antiresorptive agents such as calcitonin first and bisphosphonates (BPs) later. With the recent development of potent intravenous BPs like zoledronate, allowing a better control of disease activity over the long term with a single infusion, has contributed to a marked improvement of the clinical management of this invalidating disorder.